Kedudukan Ahlu Al-Halli wa Al-‘Aqdi dalam Pemerintahan Islam - Kadenun Kadenun (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
Ahlu al-Halli wa al-‘Aqdi are people who have the authority to loosen and bind (parse). They are the highest power holders who have the authority to direct the lives of the people to the masses. They have the authority to make laws that are binding on all people in matters that are not strictly regulated by the Qur'an and al-Hadits. And they are also a place to consult with an Imam (Leader) in determining their wisdom. The position of Ahlu al-Halli wa al-‘Aqdi in an Islamic state is to embrace the power of the people as a form of supreme power over delegations from Allah SWT. It is said that because the power is the right of the people delegated to the head of state as a party that is obliged to obey. The power of the ummah has been collected in an institution called Ahlu al-Halli wa al-‘Aqdi. In an Islamic country, such power in forming rules cannot be separated from the texts of the Qur'an and as-Sunnah. In the power of a country, this power is divided into three parts, namely: Legislative Power, Executive, and Judicative. Abu A'la al-Maududi explained with the three types of power as follows: Legislative Power is a power which is an institution based on the terminology of identical fiqh referred to as an intermediary institution and fatwa giver (Ahlu al-Halli wa al-‘Aqdi). Whereas Executive Power is the power of Ulil Amri or Umara who is tasked with upholding the guidelines of Allah SWT delivered through the Qur'an and as-Sunnah and to prepare the community to acknowledge and adhere to these guidelines to be carried out in their daily lives . The Judicial Power is the power of the judiciary (qadhaa) whose duty is to uphold God's laws in people's lives. In the power of the head of state, it can be said that Ahlu al-Halli wa al-‘Aqdi is a voter institution. The people are located as people's representatives and one of their duties is to elect a caliph or head of state. This shows that the election system of the caliph in the perspective of Islamic scholars and the tendency of Muslims in the first generation (in history) is indirect election or through representatives. In this case, functionally the same as the People's Consultative Assembly (MPR) in Indonesia as the highest state institution and representative body of the people whose personalities are people's representatives, elected by the people through an Election (General Election). One of the tasks is to elect the president (as head of state and head of government).